Perhitungan Rugi – Rugi Daya Saluran Distribusi Feeder Bangau Sakti Pada Gi Garuda Sakti PT. PLN (Persero) - Taufiq, M; Suwitno, Suwitno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Electrical power cannot be distributed properly to consumers due to the power losses that occur caused by technical and non-technical problems. The unbalance loads of distribution power system channel can happen caused by permanent conductive resistance. Good conductor should not have resistance value, but in reality every object has electrical resistance value. This conductive resistanve can cause the power losses besides it the condition of distribution network such as the length of the network often increased also it contribution to cause the power losses. The distribution network is more prone to disruption because the distribution of electricity to consumers is carried out continuously. Therefore it is necessary for the calculation of the power losses generated by the conductor. The calculation is carried out on a 20 kV distribution channel with a point to point calculation method. Total primary current has generated phase R is 4104,848 W, phase S is 3880,827 W and phase T is 3585,039 W. Total power losses that has generated feeder Bangau Sakti is 11570,71 W. Total percentage power losses that generated feeder Bangau Sakti is 0,223%. Keyword : Power Losses, Unbalance Load, Primary Distribution System